1998
DOI: 10.1101/gad.12.5.621
|View full text |Cite
|
Sign up to set email alerts
|

SCL/Tal-1 transcription factor acts downstream of cloche to specify hematopoietic and vascular progenitors in zebrafish

Abstract: SCL/Tal-1 is a transcription factor necessary for hematopoietic stem cell differentiation. Although SCL is also expressed in endothelial and neural progenitors, SCL function in these cells remains unknown. In the zebrafish mutant cloche (clo), SCL expression is nearly abolished in hematopoietic and vascular tissues. Correspondingly, it was shown previously that clo fails to differentiate blood and angioblasts. Genetic analysis demonstrates that the clo mutation is not linked to the SCL locus. Forced expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
268
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(292 citation statements)
references
References 34 publications
(23 reference statements)
15
268
1
2
Order By: Relevance
“…4 The close developmental relation between endothelial and hematopoietic cells within this extraembryonic structure led to the hypothesis that both cell systems are derived from a common stem cell, the hemangioblast. 5,6 This concept has been supported by several mouse knockout models in which both endothelial and hematopoietic cells were found to be deficient. 7,8 In addition, hemangioblasts have been derived from embryonic stem cells in vitro.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…4 The close developmental relation between endothelial and hematopoietic cells within this extraembryonic structure led to the hypothesis that both cell systems are derived from a common stem cell, the hemangioblast. 5,6 This concept has been supported by several mouse knockout models in which both endothelial and hematopoietic cells were found to be deficient. 7,8 In addition, hemangioblasts have been derived from embryonic stem cells in vitro.…”
mentioning
confidence: 67%
“…Recently it has been suggested that during embryonal life both hematopoietic and endothelial cells are derived from a common precursor cell, the hemagioblast. [5][6][7][8] Experimental studies provide evidence that such cells persist during postnatal life. It has been shown that endothelial cells can be derived from immature cells that have been purified from peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a lack of endothelium was tested in vivo with endothelium-deficient clo m39 mutants (69). The clo m39 allele includes deletion of lyscardiolipin acyltransferase, which is required for hemangioblast differentiation to hematopoietic and endothelial lineages (42,44,45,70). Although ren mRNA was expressed in early stage clo mutants (Fig.…”
Section: F535 Mural Renin Cells In Developing Zebrafishmentioning
confidence: 99%
“…30 The concept that SCL plays an important role in vasculogenesis is consistent with recent reports that SCL is required for normal yolk sac formation 31 and that SCL can partially rescue both vascular and haematopoietic defects in the zebrafish mutant, cloche. 32 The complex pattern of SCL expression raises important questions about the molecular mechanisms underlying lineage-restricted SCL expression in different cell types. We have therefore identified a number of regulatory elements responsible for lineage-specific expression of the murine SCL gene in erythroid and CD34 + myeloid cells.…”
Section: Introductionmentioning
confidence: 99%